On the Diagnosis and Management of Neurocutaneous Syndrome, a Toxicity Disorder from Dental Sealants - Amin, Omar M. (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
Neurocutaneous syndrome, a newly discovered toxicity disorder, is characterized by neurological sensations, pain, depleted energy, and memory loss as well as itchy cutaneous lesions that may invite various opportunistic infections. Components in the calcium hydroxide dental sealants Dycal, Life and Sealapex have been identified as sources of the observed symptoms. Sulfonamide and neurological toxicity issues are discussed, and three case histories are presented. Additional notes on zinc oxide, Fynal, IRM, and Sultan U/P sealers are also included. Diagnostic and management protocols at the Parasitology Center, Inc., are proposed.